Differences in Cytotoxicity of Lidocaine, Ropivacaine, and Bupivacaine on the Viability and Metabolic Activity of Human Adipose-Derived Mesenchymal Stem Cells. (January 2021) - Kubrova, Eva; Su, Min; Galeano-Garces, Catalina; Galvan, M. Lizeth; Jerez, Sofia; Dietz, Allan B.; Smith, Jay; Qu, Wenchun; van Wijnen, Andre J.
Abstract : Purpose: We evaluated biological effects of distinct local anesthetics on human adipose-derived mesenchymal stem cells when applied to reduce periprocedural pain during mesenchymal stem cell injections. Methods and Materials: Metabolic activity (MTS assay), viability (Live/Dead stain), and gene expression (quantitative real-time reverse-transcriptase polymerase chain reaction) were measured in mesenchymal stem cells incubated with various concentrations of lidocaine, ropivacaine, or bupivacaine during a 12-hr time course. Results: Cell viability and metabolic activity decreased in a dose, time, and substance-specific manner after exposure to lidocaine, ropivacaine, and bupivacaine, with ropivacaine being the least cytotoxic. Cell viability decreases after brief exposure (<1.5 hrs) at clinically relevant concentrations (eg, 8 mg/ml of lidocaine, 2.5 mg/ml of ropivacaine or bupivacaine). Mesenchymal stem cells exposed to local anesthetics change their expression of mRNA biomarkers for stress response (EGR1, EGR2), proliferation (MKI67, HIST2H4A), ECM (COL1A1, COL3A1), and cell surface marker (CD105). Conclusions: Local anesthetics are cytotoxic to clinical-grade human mesenchymal stem cells in a dose-, time-, and agent-dependent manner and change expression of ECM, proliferation, and cell surface markers. Lidocaine and bupivacaine are more cytotoxic than ropivacaine. Single-dose injections of local anesthetics may affect the biological properties of mesenchymal stem cells in vitro but may not affect the effective dose of MSCs in a clinical setting.